Complete physics for cambridge IGCSE (second edition) - Pople, Stephen (Oxford University Press Oxford, 2010)
"Complete Physics for Cambridge IGCSE" is an all-encompassing guide that covers the full range of physics topics, offering clear explanations, examples, and practice questions to help students succeed in the Cambridge IGCSE Physics exam.